Wheelchair skill tests in wheelchair basketball: A systematic review - Ferreira da Silva, C. M. A.; Santos Guedes de Sá, K.; Bauermann, A.; Borges, M.; de Castro Amorim, M.; Rossato M.; Gorla, J. I.; de Athayde Costa e Silva, A. (PLOS ONE, 2022)
Objectives: The aim of this study was to identify, describe and synthesize the skill tests used in wheelchair basketball. Method: A systematic review was carried out in the databases: PubMed/Medline, ScienceDirect, Scopus, Web of science and Google Scholar from inception to January 2021 with up to date in January 2022. The eligibility criteria used were Inclusion: (i) evaluation of wheelchair basketball athletes; (ii) using skill tests (defined as agility, speed, ball maneuverability, slalom, etc.) and (iii) papers needed to be written in English and published in peer-reviewed journals. Exclusion: (i) papers with poor description of the test methodology, (ii) participants not classified as wheelchair basketball athletes (less than one year of practice) and (iii) Participants were not people without disabilities. Results: Our main findings were: a) the most explored skills were pass and speed, and the most frequent test was the pass tests and sprint tests, b) Strong associations were found between sports classes and performance in field tests, c) The most used tests for each skill were: pass = pass accuracy and maximum pass; speed = 20m sprint test with and without the ball; agility = slalom test; dribbling = obstacle dribbling tests and throw = free throw and spot shot. Conclusion: The most explored skills were passing and speed, and to evaluate these skills we highlight the two-handed chest pass test, 20m sprint test with ball and the WMP test. The use of specific tests can facilitate the creation of reference standards and possible comparison of athletes and, thus, enable better training conditions, aiming to meet the specific demands of each athlete and team.